The Influence of Perceived Usefulness, Perceived Ease of Use, and Sales Promotions Exposure on the Purchase Intention of OVO - Ghaliyah Julya Almira; Tandiyo Pradekso; Nurist Surayya Ulfa (Interaksi Online, 2022)
The usage of digital wallets and non-cash purchase transaction are becoming increasingly popular among Indonesians. It showed by the increased number of economic transactions using online payment, that Bank Indonesia claimed has grown 20% on November 2020. One famous brands for this digital money service is OVO. Due to its partnership with Tokopedia, an Indonesian e-commerce site, OVO has been the most prominent digital payment brand Since 2019 for e-commerce payment. Whilst now the digital payment services become more competitive, OVO’s position as the market leader has been overtook by GoPay in 2021, and then now by ShopeePay. Thus, this study aims to determine the effect of OVO's perceived usefulness, perceived ease of use and sales promotion on the purchase intention using OVO. The hypotheses in this study are derived from the theory of Technology Acceptance Model and Advertisement Theory This study used online survey to 100 males and females, aged 22-35 years old, in Indonesia and used e-wallets which were chosen by the method of non-probability sampling technique. The results showed that the hypothesis about perceived usefulness and perceived ease of use is accepted with a significance value of 0.000, indicating there is a significant influence on purchase intention but only perceived usefulness significantly influences purchase intention. Furthermore, the second hypothesis is rejected where OVO’s sales promotion exposure has a significance value of 0.755, meaning there is no significant influence.